MODEL OPTIMASI POLA TANAM PADA LAHAN KERING DI DESA SARIMUKTI KECAMATAN PASIRWANGI KABUPATEN GARUT - Roni Kastaman; Dwi Rustam Kendarto; Awan Mustafa Aji (Teknotan: Jurnal Industri Teknologi Pertanian, 2007)
Garut residence, as one of the main agriculture area in West Java Province, in the year of 2001 Garut government has decided to developed dry land plants, because the dry land has an extensive area compared to the wet land area in Garut. In contrast the income of the dry land farmers are remaining low. The research was carried out on March to September 2006. The aim of this research is to decide the optimal plantation pattern so can gain a maximal profit, and also find out the level of farmer’s earning before and after the optimizing process was conducted. Alternative patterns of plantation which can be developed are potatoes, cabbage, string bean, mustard greens, peas and red pepper chili for first plantation season. In the second plantation, the optimal patterns are cabbage, mustard greens and cauliflower.   In the third plantation season, the alternative pattern is potato, cauliflower, string bean and mustard greens. Keywords:  Garut, optimized pattern of plantation